The Future of the Indo-Pacific Security Architecture: A Scenario Planning Approach in Response to U.S. Foreign Policy in the Age of Trump 2.0 - Meyta Saraswaty Putri (Jurnal Impresi Indonesia, 2025)
President Donald Trump's second presidency marks a significant shift in the foreign policy orientation of the United States, which has had a far-reaching impact on the security configuration in the Indo-Pacific region. This study aims to analyze the impact of Donald Trump's leadership on U.S. foreign policy and its implications for the security dynamics of the Indo-Pacific region. Using a literature review approach and scenario planning framework, this study examines the adaptive responses of countries in the Indo-Pacific region in the face of geopolitical uncertainty posed by Trump's unilateralist and "America First" policies. By integrating PESTLE analysis and regional security theory, the study maps four possible future strategic scenarios: Fortress Pacific, Hedging Archipelago, Echo Chamber Alliance, and Age of Disorder. The results show that regional nations are seeking to strengthen regional self-reliance and cooperation, while mitigating the uncertainty of U.S. security commitments that have the potential to undermine regional stability. This paper provides conceptual contributions in the form of adaptive scenario-planning-based analytical models, as well as offers strategic recommendations for Indo-Pacific countries in dealing with the dynamics of great power rivalry in the post-Trump era.